ANALISIS PENDAPATAN PETANI GULA KELAPA DAN MITIGASI PERUBAHAN IKLIM - Hilda Zulhida, Evi Gravitiani (Journal of Agriculture, Resource and Environmental Economics, 2019)
Research aims to determine impact of climate change as among the factors which affect the income palm sugar Farmers located in Karanggadung Village Petanahan Sub District and Rangkah Village Buayan Subdistrict, Kebumen District.Research include descriptive through surveys use of cluster sampling method. Total of 200 palm sugar Farmers located in Karanggadung Village Petanahan Subdistrict and Rangkah Village Buayan Subdistrict, Kebumen District became sample. Data analysis technique used for hypothesis test are Multiple Linear Regression, agribusiness analysis and descriptive statistics analysis.Results of analysis by use of Multiple Linear Regression showed that the independent variables age, production, business cost and The Man Working (HOK) simultaneously have a significant and positive impact on the income palm sugar Farmers. Results of palm sugar agribusiness analysis can be said sufficient daily for palm sugar Farmers located in Karanggadung Village, Petanahan Subdistrict and Rangkah Village Buayan Subdistrict. Third results analysis which uses the statistics descriptive analysis for climate change mitigation by the Farmers been good enough conducted by watering coconut trees and provides fertilizer during the dry season therefore a lot of sap produced, but still a few Farmers who undertake mitigation. Average of palm sugar Farmers permit the plants during the dry season therefore less sap produced and it affects the income of palm sugar Farmers.